An analysis of relationship between gold price and U.S. dollar index by using bivariate extreme value copulas - Mutita Kaewkheaw (2018)
In this study, we analyse the behaviour of the gold price and U.S. dollar index by using bivariate extreme value and extreme value copulas. For measuring the dependence structure between the returns on gold price and U.S. dollar index, the paper uses the extreme value copula theory. This study presents the result that the returns on gold price and the U.S. dollar index are independence in the extreme. © Springer International Publishing Switzerland 2014.